Thyroid cancer: mortality rate analysis during the period 2017-2021 in Chile - Concha Espinosa, Camila; Muñoz Leiva, Khatalina; Muñoz Chávez, Sebastián; Oyarzún Cárcamo, Tomás; Torrealba Bustos, Andrés (Revista Chilena de Estudiantes de Medicina, 2024)
Introduction: Thyroid cancer has experienced an increase in its incidence. Studies have suggested that this rise in incidence is due to incidental detection, as well as other environmental, nutritional, and genetic risk factors. Objective: To describe the mortality rate from thyroid cancer in Chile between the years 2017-2021. Materials and methods: This is an ecological and descriptive study involving a study population of 746 patients, both male and female, over 15 years of age, whose cause of death was thyroid cancer between the years 2017-2021 in Chile. Data collected from the Department of Statistics and Health Information and the 2017 Census were used to calculate the mortality rate by year, sex, and age group using Microsoft 365 Excel®. Results: A total of 746 deaths due to thyroid cancer were studied, with a mortality rate of 1.06 per 100.000 inhabitants in the period 2017-2021. The most affected age group was 80 years and older. Discussion: Thyroid cancer has shown a notable increase in incidence worldwide. The results obtained show a mortality rate higher than that reported by another study in 2020.